Psychospiritual in palliative care services: a literature review - I Putu Candra Sasmita Sutarta; Ni Ketut Putri Ariani (Intisari Sains Medis, 2022)
Background: Palliative care provide holistic services at the physical, mental, and spiritual levels. Spiritual care is an intrinsic and essential component of palliative care that WHO has recognized. However, spiritual care is still not widely known by the community and health workers in the practice of palliative care. Methods: This literature review was written based on various books, journals, and scientific articles that related to spiritual care in palliative care. The quantitative and qualitative data were obtained, then collected and sorted into a report based on the appropriate topic. Result: Spirituality is one of the fundamental dimensions in the quality of life and maintaining culture. Thus, spirituality is an important component of palliative care. Many palliative patients understand their spiritual needs and want health professionals to help them address these needs. Various existing studies show that spiritual care provides benefits, especially in emotional needs and the search for meaning in life at the end of life. Palliative care professionals can provide spiritual care, but spiritual care is complex and requires specialized knowledge, expertise, and experience in assessing and meeting patient needs, requiring further training and education. Conclusion: Various studies have shown that palliative patients need psychospiritual care to support comfort and meaning in their lives towards the end of life. So, psychospiritual care in palliative care needs to be implemented and improved, especially in training for palliative care teams.